Produksi Karya Musik “The Story of Tapa Malenggang” (Production of Musical Works "The Story of Tapa Malenggang") - aby rahman; Yon Hendri; Nora Anggraini (MUSICA : Journal of Music, 2022)
Tujuan artikel ini adalah untuk menjabarkan proses kerja produksi karya musik The Story of Tapa Malenggang.Tapa Malenggang merupakan sastra lisan yang berasal dari Kabupaten Batanghari, Desa Tanjung, Maruo Provinsi Jambi. Tapa Malenggang mempunyai nama asli yaitu Mambang Diawan yang hidup dipintu langit merupakan sebuah ritual. Dalam ritual Tapa Malenggang, terdapat dendang yang dihadirkan sebagai bentuk syukur dan terima kasih atas kebaikan Tapa Malenggang yang telah menjaga kedamaian masyarakat disekitar sungai Batanghari. Pengkarya tertarik untuk mengangkat cerita Tapa Malenggang dengan mengadodpsi sepenggal melodi dendang ke dalam konsep musik elektro-akustik dan menggunakan beberapa teknik-teknik sound design. Elektro-akustik merupakan suara atau bunyi yang terdengar, tidak lagi terlihat sumber aslinya. Metode yang di gunakan dalam artikel ini adalah pengolahan elektro-akustik menggunakan beberapa teknik sound design seperti audio synthesis yang meliputi wave shape, LFO dan volume envelope. Hasil yang diperoleh dalam artikel ini adalah gambaran proses kerja dalam produksi karya musik The Story of Tapa Malenggang.ABSTRACTThe purpose of this article is to describe the work process of producing the musical work The Story of Tapa Malenggang. Tapa Malenggang is an oral literature originating from Batanghari Regency, Tanjung Village, Maruo, Jambi Province. Tapa Malenggang has a real name, namely Mambang Diawan, who lives at the door of the sky as a ritual. In the Tapa Malenggang ritual, there is a song that is presented as a form of gratitude and thanks for the kindness of Tapa Malenggang who has kept the peace of the community around the Batanghari river. The authors are interested in bringing up the story of Tapa Malenggang by adopting a piece of dendang melody into the concept of electro-acoustic music and using several sound design techniques. Electro-acoustic is a sound or sound that is heard, no longer seen the original source. The method used in this article is electro-acoustic processing using several sound design techniques such as audio synthesis which includes wave shape, LFO and volume envelope. The results obtained in this article are an overview of the work process in the production of the musical work The Story of Tapa Malenggang.